1995
DOI: 10.1111/j.1477-9552.1995.tb00764.x
|View full text |Cite
|
Sign up to set email alerts
|

Causality Between Productivity and Exports in Agriculture: Evidence From Asia and Latin America

Abstract: This paper examines the causal relationship between agricultural productivity and exports for selected Asian and Latin American countries. Alternative views about the causal relationship between these variables of economic interest exist. Economic theory provides no firm basis to judge whether productivity causes exports or exports cause productivity (export‐led growth). Since this issue is empirical, econometric tests are utilised to investigate the nature of this causality. Test results are mixed although th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
24
0
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 10 publications
2
24
0
1
Order By: Relevance
“…In relation to the countries that are of specific interest to this study, there have been fourteen time-series empirical studies examining the relationship between exports and economic growth for South Korea (Jung and Marshall, 1985;Chow, 1987;BahmaniOskooee et al, 1991;Bahmani-Oskooee and Alse, 1993;Dodaro, 1993;Arnade and Vasavada, 1995;Dutt and Ghosh, 1996;Riezman et al, 1996;Rahman and Mustafa, 1997;Islam, 1998;Ekanayake, 1999;Anoruo and Ramchander, 2000;Kónya, 2004;Awokuse, 2005a). However, among these studies only Bahmani-Oskooee and Alse (1993) and Awokuse (2005a) use quarterly data and both find evidence of bi-directional causality.…”
Section: Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…In relation to the countries that are of specific interest to this study, there have been fourteen time-series empirical studies examining the relationship between exports and economic growth for South Korea (Jung and Marshall, 1985;Chow, 1987;BahmaniOskooee et al, 1991;Bahmani-Oskooee and Alse, 1993;Dodaro, 1993;Arnade and Vasavada, 1995;Dutt and Ghosh, 1996;Riezman et al, 1996;Rahman and Mustafa, 1997;Islam, 1998;Ekanayake, 1999;Anoruo and Ramchander, 2000;Kónya, 2004;Awokuse, 2005a). However, among these studies only Bahmani-Oskooee and Alse (1993) and Awokuse (2005a) use quarterly data and both find evidence of bi-directional causality.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, among these studies only Bahmani-Oskooee and Alse (1993) and Awokuse (2005a) use quarterly data and both find evidence of bi-directional causality. In contrast, over a third apply a multivariate analysis which supports the hypotheses of export-led growth (Riezman et al, 1996;Islam, 1998), growth-led exports (Arnade and Vasavada, 1995), bi-directional causality (Anoruo and Ramchander, 2000;Awokuse, 2005a) and increased output growth leading to reduced exports (Kónya, 2004). Additionally, when undertaking bivariate analysis, studies reported bi-directional causality (Chow, 1987;Bahmani-Oskooee et al, 1991;Bahmani-Oskooee and Alse, 1993;Rahman and Mustafa, 1997;Ekanayake, 1999), non-causality (Dodaro, 1993;Dutt and Ghosh, 1996;Riezman et al, 1996;Islam, 1998) and that increased output growth leads to a decrease in export growth (Jung and Marshall, 1985;Kónya, 2004).…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations